417 GASTRIC CONDUIT FISTULA AFTER ESOPHAGECTOMY: WHY IT HAPPENS AND HOW TO MANAGE. (14th September 2020) - Bianchi, E; Tustumi, F; de Miranda Neto, A; Duarte, A; Seguro, F; Szachnowicz, S; da Rocha, J; Sallum, R; Cecconello, I
Abstract:  : Gastric tube fistula is a rare event, but very feared, as it invariably progresses with associated mediastinitis and can be fatal. We present a case in which this fistula occurred together with all diagnostic investigation of etiology and treatment, in addition to a brief review of this complication. Methods: A 45-year-old patient underwent minimaly invasive esophagectomy due to end-stage achalasia. After 6 days, she presented acute multivisceral migration to the chest and needed to reintervation by open surgery and hiatoplasty. The patient evolved with outflow of bile through the chest drain. Conservative treatment was attempted. However, after 4 days, she underwent thoracotomy and suture of the orifice, and a nasal tube was maintained to drain the gastric tube. There was no suture dehiscence and in control a seriogram evidenced pyloric stenosis. After 2 months, she was submitted to GPOEM with improvement of gastric emptying and normal return to feeding. Results: The risk factors for gastric tube fistula are the same as those for cervical or intrathoracic anastomosis fistula after esophagectomy. Some authors attribute the vascularization of the stomach and malnutrition. However, as shown in this case, impairment of gastric emptying is an important factor to increased pressure and consequent fistula. The patient experienced acute migration through the hiatus, which obstructed the tube for a few hours. And after the defect was corrected, he maintained an increased pressure due to pyloric achalasia, which was initially treated by depressurizing the tube by nasogastric tube and then GPOEM. Conclusion: Gastric tube fistula can be avoided when we can establish a good gastric tube emptying condition.